Seniorzy na terenach wiejskich – możliwości i ograniczenia rozwoju - Sienkiewicz-Wilowska, Julia Anastazja (Studia Edukacyjne, 2020)
Late adulthood is a time when the elderly living in rural areas are especially at risk of exclusion. Very often they have difficultiesaccessing aid institutions and activities which are designed specificallyfor them. Often their functioning depends on good relations with neighbors and the family. Opportunities to increase their social participation and use of their resources include the activities of organizations such as the Rural Housewives’ Circle, or entrusting them with the function of local community leaders.